2022
DOI: 10.3389/fmicb.2022.964156
|View full text |Cite
|
Sign up to set email alerts
|

P25 and P37 proteins encoded by firespike leafroll-associated virus are viral suppressors of RNA silencing

Abstract: Firespike leafroll-associated virus (FLRaV) is a major pathogen associated with firespike (Odontonema tubaeforme) leafroll disease. Phylogenetic analysis showed that FLRaV possesses typical traits of subgroup II members of ampeloviruses, but encodes two additional proteins, P25 and P37. Here, we determined the microfilament localization of P25 protein. Posttranscriptional gene silencing (PTGS) assay showed that both FLRaV P25 and P37 were able to suppress the local and systemic PTGS and FLRaV P25 was capable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…In this study, the potential RSS abilities of six proteins encoded by CCDaV were screened by co-agroinfiltration with pART27-eGFP in 16c plants; CCDaV-V2 exhibited the ability to suppress local and systemic RNA silencing. V2 could not suppress intercellular movement of RNA silencing, indicating that the ability of V2 to suppress PTGS is not through direct binding of siRNAs ( Wang et al, 2022 ). Some studies also showed that V2 encoded by MMDaV, along with p25 and p37 encoded by firespike leafroll-associated virus (FLRaV), could suppress local RNA silencing and long-distance movement of the silencing signal in 16c plants, while not affecting short-distance movement of the silencing signal ( Yang et al, 2018 ; Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the potential RSS abilities of six proteins encoded by CCDaV were screened by co-agroinfiltration with pART27-eGFP in 16c plants; CCDaV-V2 exhibited the ability to suppress local and systemic RNA silencing. V2 could not suppress intercellular movement of RNA silencing, indicating that the ability of V2 to suppress PTGS is not through direct binding of siRNAs ( Wang et al, 2022 ). Some studies also showed that V2 encoded by MMDaV, along with p25 and p37 encoded by firespike leafroll-associated virus (FLRaV), could suppress local RNA silencing and long-distance movement of the silencing signal in 16c plants, while not affecting short-distance movement of the silencing signal ( Yang et al, 2018 ; Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…V2 could not suppress intercellular movement of RNA silencing, indicating that the ability of V2 to suppress PTGS is not through direct binding of siRNAs ( Wang et al, 2022 ). Some studies also showed that V2 encoded by MMDaV, along with p25 and p37 encoded by firespike leafroll-associated virus (FLRaV), could suppress local RNA silencing and long-distance movement of the silencing signal in 16c plants, while not affecting short-distance movement of the silencing signal ( Yang et al, 2018 ; Wang et al, 2022 ). These results are similar to the results of the present study, and this finding enriches our understanding of the functions of proteins encoded by geminiviruses.…”
Section: Discussionmentioning
confidence: 99%
“…After confirmation by sequencing, the constructed plasmids and empty vector were individually transferred into the Agrobacterium tumefaciens strain GV3101 by electroporation, as described previously [47,48]. The Agrobacteriummediated inoculation of N. benthamiana was performed as described previously [49,50]. Simultaneously, the PVX-based vector expressing a green fluorescent protein (GFP) (PVX:GFP) was used as a vector control.…”
Section: Pvx Construct and Viral Inoculationmentioning
confidence: 99%
“…Further amino acid sequence alignment of CRPs showed that CiCV1-CN CRP had a conserved Carlavirus nucleic acid binding domain (IPR002568, 8-92 aa) (Figure 4b). Furthermore, CiCV1-CN CRP was also predicted to have an arginine-rich NLS motif ( 47 RRRR 50 ) and a ZF motif ( 57 CX2CX12CX4C 78 )…”
Section: Phylogenetic and Sequence Analyses Of Crp Proteins Of Carlav...mentioning
confidence: 99%
“…However, silencing of GFP induced this way can be suppressed by the simultaneous expression of VSRs (Voinnet et al, 1999). This method has been used to identify VSRs among virus-encoded proteins for decades (Brigneti et al, 1998;Voinnet et al, 1999;Qu et al, 2003;Cui et al, 2005;Li et al, 2014;Dong et al, 2016;Sinha et al, 2021;Wang et al, 2022). Green fluorescence was observed under a long wavelength (365 nm) using a hand-held UV lamp raised 6 inches above the plants at four days post infiltration (dpi) in the dark room.…”
Section: Examination Of Fluorescence In Plantsmentioning
confidence: 99%